qirā ’ah ’awwalīyah lil-ruqum al-mismārīyah al-muktašafah fī Tall al-Šaiḫ Ḥamd ’alā al-Ḫābūr - Rūlīǧ, Wulfǧānǧ
Wolfgang Röllig; Preliminary Reading of the Cuneiform Archives Discovered at Tall Šai? ?amd on the ?abur; ersch. 1986?; in Arabic; translated and abridged by Q?sim ?uwair.